A Comparative Study on Lilit Phra Lo and Butterfly Lovers: Symbols and Representation of Ideologies in Thai and Chinese Socio-cultural Perspectives - Aiewnoi, Thitiyakorn; Samara Yarapirom, Pim (Journal of International Studies, Prince of Songkla University, 2024)
This study examined symbols and representations of ideologies and belief systems as well as similarities and differences of ideological perspectives, religious influences, and socio-cultural contexts in Lilit Phra Lo and Butterfly Lovers. This study applied a qualitative method by collecting secondary data and related research via documents and analytical descriptions of the socio-cultural context using a comparative approach and a content analysis approach to analyze the selected sample. Lilit Phra Lo represents syncretism of animist beliefs or supernatural power with Buddhism and Hinduism, which shape the identity of Thai culture. Butterfly Lovers, a Chinese folktale, reflects the elements of Confucianism and Taoism, the core of traditional Chinese society. Both tales play a significant role in reflecting ideologies and belief systems and constructing the cultural values in Thailand and China. The analysis indicates that both cultures cultivate respecting elders and obeying parents; however, there are several differences in ideological and religious influence due to social and cultural contexts. Chinese philosophies emphasize the principle of living harmoniously in society, but Thai people believe in the cause and effect of action. Moreover, both tales conveyed inequality and implications of gender hierarchy under a patronage system and a patriarchal society.